Ecofriendly microencapsulated phase-change materials with hybrid core materials for thermal energy storage and flame retardancy - Hu, Zhong-Ting (2022)
Microencapsulated phase-change material (ME-PCM) employing octadecane as a core material has been practiced for thermal-energy-storage (TES) applications in buildings. However, octadecane as a hydrocarbon-based PCM is flammable. Herein, silica-shelled microcapsules (SiO2-MCs) and poly(urea-formaldehyde)-shelled microcapsules (PUF-MCs) were successfully prepared, loaded with octadecane/tributyl phosphate (TBP) as hybrid core materials, which not only exhibited good TES properties but also high-effective flame retardancy. SiO2-MC (ΔHm = 124.6 J g-1 and ΔHc = 124.1 J g-1) showed weaker TES capacity than PUF-MC (ΔHm = 186.8 J g-1, ΔHc = 188.5 J g-1) but better flame retardancy with a lower peak heat-release rate (HRRpeak) of 460.9 W g-1 (556.9 W g-1 for PUF-MCs). As compared with octadecane (38.7 kJ g-1), the reduction in total heat release (THR) for SiO2-MC was up to 22% (30.1 kJ g-1) with combustion time shortened by 1/6. SiO2-MC had a typical diameter of 150-210 μm, shell thickness of ∼6.5 μm, and a core fraction of 84 wt %. SiO2-MC showed better thermal stability with a higher initial evaporation/pyrolysis temperature than PUF-MC. The thermal decomposition of MCs with its mechanism of flame retardancy was significantly studied using thermogravimetric analysis/infrared spectrometry (TG-IR). The strategy presented in this study should inspire the development of microcapsules with PCMs/flame retardants as hybrid core materials for structural applications.